Quality of Service in Making Land Certificates at the Mamuju Regency Land Office - Andi Arini Aswani (Journal of Education Technology Information Social Sciences and Health, 2024)
This research aims to describe and analyze the quality of service in making land certificates at the Mamuju Regency Land Office. Considering that the Land Office is a government agency that provides land certificate services, quality services are needed so that people who do not yet have land certificates want to certify their land. The method used in this research is a qualitative descriptive research method. There were five informants in this study. The data collection techniques used were in-depth interviews, participant observation and documentation studies. The indicators used are (1) Direct evidence (2) Reliability (3) Responsiveness (4) Assurance (5) Empathy. The results of this research show that the quality of service in making land certificates at the Mamuju Regency Land Office is quite good in providing services, however the facilities do not appear to be good enough and there are still many complaints about how long the process of making land certificates is due to network problems.